REORIENTASI PERAN PEMERINTAH DALAM PEMBANGUNAN EKONOMI DI TENGAH ARUS KEKUATAN MODAL - Gedeona, Hendrikus Triwibawanto (Pusjar SKPP Lembaga Administrasi Negara, 2007)
Economic development policy for improving social welfare and nation-building should become one of the main concerns of both local and central governments. So far, development orientation has tended to benefit big capital owners rather than satisfying citizens’ interest. The formulation and implementation of economic policy has neglected one of the nation goals, i.e social justice. Therefore, in order growth with redistribution development to materialize, local and central governments have to fulfil and protect the very basic needs of their citizens. In addition, empowerment, partnership and rule of law enforcement become the prerequisite to safeguard citizens from the negative impacts of development. Keywords : Reorientasi Peran Pemerintah, Pembangunan Ekonomi